A survey of the dialect geography of five towns and one city in Nueva Ecija (Gapan, General Tinio, Munoz, San Isidro, San Leonardo and Cabanatuan City) - Ang, Juliana Pangilinan 1950- (s.n., 1973)
This study makes up for another volume of the dialect geography of the Philippine languages. It shows the word variations of Tagalog, as spoken in five towns and one city of Nueva Ecija, Gapan, General Tinio, Mu¤oz, San Isidro, San Leonarde, and Cabanatuan City. The survey was primarily concerned in finding out the varieties in form of words having similar meanings based on the geographical location of the linguistic communities and age levels of the informants.